2021
DOI: 10.3389/fonc.2021.742037
|View full text |Cite
|
Sign up to set email alerts
|

Tumor DNA From Tumor In Situ Fluid Reveals Mutation Landscape of Minimal Residual Disease After Glioma Surgery and Risk of Early Recurrence

Abstract: The recurrence of glioma is a difficult problem in clinical treatment. The molecular markers of primary tumors after resection cannot fully represent the characteristics of recurrent tumors. Here, abundant tumor DNA was detected in tumor in situ fluid (TISF). We report that TISF-derived tumor DNA (TISF-DNA) can detect genomic changes in recurrent tumors and facilitate recurrence risk analysis, providing valuable information for diagnosis and prognosis. The tumor DNA in TISF is more representative and sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…These suggest that, to some extent, TISF is reliable for detecting somatic variants during systemic treatment of gliomas and can be used as an alternative to tissue analysis and to obtain accurate genomic information on the recurrent tumour. 5 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…These suggest that, to some extent, TISF is reliable for detecting somatic variants during systemic treatment of gliomas and can be used as an alternative to tissue analysis and to obtain accurate genomic information on the recurrent tumour. 5 …”
Section: Figurementioning
confidence: 99%
“…These suggest that, to some extent, TISF is reliable for detecting somatic variants during systemic treatment of gliomas and can be used as an alternative to tissue analysis and to obtain accurate genomic information on the recurrent tumour. 5 In the cohort of 20 patients (time from patients' postoperative period to imaging suggestive of progressive disease (PD), shown in Figure S2C) with serial TISF samples collected prior to PD, we compared the 20 patients with top mutated genes between BL and last TISF before PD, showing that most patients had a significantly altered number of mutated genes at PD (Figure 2A,B,E), with a significant change in clearance and acquisition rates of top mutated genes like GNAS/CIC (Figure 2C), and generating an actionable target map for postoperative gliomas (Figure 2D). Furthermore, we found that MVAF was also differentially increased or decreased in TISF at PD compared to BL (Figure 2E), with more significant changes in VAF < 1% in genes with an increased number of mutations (Figure 2F).…”
mentioning
confidence: 99%
“…circulating tumor cells (CTCs), platelets) [56,60]; circulating nucleic acids (eg. cell-free DNA (CfDNAs) [61], circulating tumor DNA (ctDNA) [62], and protein markers (e.g., hypermethylation) [8,63], all of which can allow for real-time monitoring and have been analyzed concerning response in glioma [54]. Hypermethylation, treatment, and survival are intertwined entities complicating imaging and biomarker analysis [64].…”
Section: Are There Potentially Other Data Sources That May Help Answe...mentioning
confidence: 99%
“…The tumor tissue is obtained intraoperatively, TISF is obtained by the treatment pump and sample analysis. See the method [12,13,15].…”
Section: Patients and Sample Collectionmentioning
confidence: 99%
“…In response to this worldwide problem, we propose a CTT solution [11]. Our previous research showed that TISF ctDNA was a powerfully potential source for characterizing the genomic landscape of glioma [12],and reveals the mutational landscape of minimal residual disease after glioma surgery and the risk of early recurrence [13].The aims of this study were rstly to determine whether postoperative recurrence-free survival is associated with mean VAF for mutant genes. Secondly, responses associated with postoperative TMZ chemotherapy, including evaluate treatment effect by comparing TISF ctDNA with corresponding imaging and early detection of hypermutation during TMZ treatment, besides by performing serial TISF testing in two hypermutated patients, we reproduced the in vivo evolution from early postoperative period to TMZ-induced MMR loss and eventual hypermutation to relapse.…”
Section: Introductionmentioning
confidence: 99%